2022
DOI: 10.26434/chemrxiv-2022-sgxr4
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Are Vanadium Intermediates Suitable Mimics in Non-Heme Iron Enzymes? An Electronic Structure Analysis

Abstract: Vanadyl intermediates are frequently used as mimics for the fleeting Fe(IV)=O intermediate in non-heme iron enzymes that catalyze C–H activation. Using density functional theory and correlated wavefunction theory, we investigate the degree to which vanadium mimic electronic structure is comparable to catalytic iron intermediates. Our calculations reveal crucial structural and energetic differences between vanadyl and ferryl intermediates primarily due to differences in ground spin states of low spin and high s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 104 publications
(143 reference statements)
1
4
0
Order By: Relevance
“…hydrogens are slightly closer to the metal than the C6 exo hydrogen that is the primary H• donor to the ferryl complex emphasizes the importance of approach angle to HAT efficiency. This notion was first put forth in our work on the halogenase SyrB2, 29 has been supported by multiple computational studies reported since, 32,54,57 and is discussed in more detail below. For the HnH6H•V IV O•succ•7-d1-Hyo complex, the angle relating the g-tensor of the vanadyl spin probe and the metal-deuterium vector was also accessible by analysis of the magnetic field-dependence of the spectra (Figure S15-S21).…”
Section: Multiple Crystallographic Views Of the Abh6h Active Site Imp...supporting
confidence: 61%
See 4 more Smart Citations
“…hydrogens are slightly closer to the metal than the C6 exo hydrogen that is the primary H• donor to the ferryl complex emphasizes the importance of approach angle to HAT efficiency. This notion was first put forth in our work on the halogenase SyrB2, 29 has been supported by multiple computational studies reported since, 32,54,57 and is discussed in more detail below. For the HnH6H•V IV O•succ•7-d1-Hyo complex, the angle relating the g-tensor of the vanadyl spin probe and the metal-deuterium vector was also accessible by analysis of the magnetic field-dependence of the spectra (Figure S15-S21).…”
Section: Multiple Crystallographic Views Of the Abh6h Active Site Imp...supporting
confidence: 61%
“…License: CC BY-NC-ND 4.0 configurations of the reactant complexes and by reproducing substrate-association/dissociation dynamics of the ferryl complexes more closely than do the reactant complexes. 5,15,30,36,[51][52][53] More recent computational work employing density function theory (DFT) to estimate relative coordination energies in small active-site models has raised caveats regarding the fidelity of ferryl mimicry by vanadyl, 36,54 but these studies have neither provided alternative explanations for the experimental correlations of structure to reaction dynamics/outcomes nor accounted for the possibility that the larger protein structure could override small energetic differences in intrinsic propensity of the metal and ligands to adopt a certain coordination geometry. We solved structures from crystals of the AbH6H•V IV O•succ•Hyo and AbH6H•V IV O•succ•6-OH-Hyo complexes, the latter the first example of the use of the vanadium cofactor mimic to provide structural insight in a native non-hydroxylation reaction.…”
Section: Multiple Crystallographic Views Of the Abh6h Active Site Imp...mentioning
confidence: 99%
See 3 more Smart Citations